Increased Leptin/Leptin Receptor Pathway Affects Systemic and Airway Inflammation in COPD Former Smokers [Retraction] - Bruno A; Alessi M; Soresi S; Bonanno A; Riccobono L; Montalbano AM; Albano GD; Gjomarkaj M; Profita M (Dove Medical Press, 2021)
Bruno A, Alessi M, Soresi S, et al. J Inflamm Res. 2011;4:51–59. The Editor and Publisher of Journal of Inflammation Research wish to retract the published article. Concerns were raised regarding the duplication of images in Figure 3 describing leptin receptor expression with those from an article published by the authors several years previously describing muscarinic receptor expression. Specifically: Figure 3A, Leptin receptor expression, Smokers, appears to have been duplicated with Figure 2 panel M3 COPD, for the expression of muscarinic receptors. Figure 3D, Leptin expression, Smokers, appears to have been duplicated with Figure 2 panel M1 Smokers, for the expression of muscarinic receptors. Figure 3A, Leptin receptor expression, Smokers, appears to share duplicated elements with Figure 3D, Leptin expression, Smokers. The authors did not respond to our queries and the Editor advised for the article to be retracted. Our decision-making was informed by our policy on publishing ethics and integrity and the COPE guidelines on retraction. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”. This retraction relates to this paper